Exploring the critical factors of depot maintenance on weapon systems in South Korea - Yongdo Hur (선진국방연구)
Weapon system maintenance is essential for ensuring the operational availability of equipment while enhancing its performance and quality. Depot maintenance, as a core component of national defense logistics, involves the periodic disassembly, repair, and performance enhancement of weapon systems that have reached their endurance limits during the wear-out failure. It is critical for sustaining performance and achieving target operational rates. However, the current depot maintenance strategy in the Korean military primarily relies on the bathtub curve model, which may inadequately reflect variations in failure rates caused by differences in operating environments and sub-component characteristics. In addition, aging maintenance infrastructure and escalating costs of advanced weapon systems pose significant challenges to meeting operational targets. To overcome these limitations, a proactive approach is needed—one that prepares maintenance facilities and support equipment in advance, integrates depot maintenance with performance upgrades, and reduces unnecessary resource consumption. Enhancing the depot maintenance strategy is vital for improving the operational readiness of weapon systems and advancing the expertise of national defense operations. The current study identifies key factors affecting the effectiveness of depot maintenance and presents a research model designed to enhance weapon system operational rates and strengthen defense capabilities. By accurately determining equipment life cycles and incorporating performance improvements, the proposed model offers actionable insights for optimizing depot maintenance strategies in contemporary military operational environment.